1985
DOI: 10.1037/0278-7393.11.1.126
|View full text |Cite
|
Sign up to set email alerts
|

Semantic activation of noun concepts in context.

Abstract: A modified Stoop procedure was used to examine the role that context plays in guiding semantic access of unambiguous nouns in sentence contexts. The sentences either emphasized a high-or a low-dominant property of a noun that was the last word in the sentence or were control sentences. Each sentence was followed by the relevant high-or low-dominant property either immediately or after a 300or a 600-ms delay. There was significant color-naming interference (relative to control) for high-dominant properties rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
3
8

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 22 publications
4
71
3
8
Order By: Relevance
“…This finding contradicts 'constructivist' theories that claim that categories do not possess a relatively fixed internal structure and that the meaning of a category can change dramatically, depending on the context in which the name of the category is immersed (Anderson et al 1976;Anderson and Shiffrin 1980). For the present question of when context influences category structure, Whitney et al 1985 work is most relevant because it entailed an on-line investigation of processing using Cross Modal Lexical Priming (CMLP). CMLP, which has also been used in some of the studies of lexical access mentioned previously, is based on the semantic priming effect: Words closely associated with previously perceived words will be recognized faster than unrelated words (see, e.g., Neely 1977).…”
Section: Category Names In Sentential Contextcontrasting
confidence: 40%
See 2 more Smart Citations
“…This finding contradicts 'constructivist' theories that claim that categories do not possess a relatively fixed internal structure and that the meaning of a category can change dramatically, depending on the context in which the name of the category is immersed (Anderson et al 1976;Anderson and Shiffrin 1980). For the present question of when context influences category structure, Whitney et al 1985 work is most relevant because it entailed an on-line investigation of processing using Cross Modal Lexical Priming (CMLP). CMLP, which has also been used in some of the studies of lexical access mentioned previously, is based on the semantic priming effect: Words closely associated with previously perceived words will be recognized faster than unrelated words (see, e.g., Neely 1977).…”
Section: Category Names In Sentential Contextcontrasting
confidence: 40%
“…Other work on conceptual categorization in a sentential context was carried out by Whitney and colleagues (Whitney 1986;Whitney and Kellas 1984;Whitney et al 1985). In their 1984 study using the Stroop effect, Whitney and Kellas showed that when category names are encountered in a sentence they do not seem to be encoded as particular (contextually congruent) exemplars.…”
Section: Category Names In Sentential Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…It is conceivable that even at the lexical level only a shallow semantic access occurs in natural reading. Combining this view with the hypothesis that words have a "core" meaning that is automatically and rapidly activated (Whitney et al, 1985;Mahon and Caramazza, 2008;Dove, 2009), perhaps only this core meaning is activated in natural reading. On this view, common single-word experimental settings result in an unusually deep and/or wider processing of the concept, resulting in activation of "peripheral" semantic features, which may be grounded in sensory-motor cortices but do not represent the core aspects of the meaning, whatever they are.…”
Section: Number Of Total Fixations Number Of Fixations On Nouns Fixatmentioning
confidence: 99%
“…In a series of studies, Whitney and his colleagues (Whitney, 1986;Whitney & Kellas, 1984;Whitney, McKay, Kellas, & Emerson, 1985) examined lexical access using the Stroop task. Initially, Whitney and KeUas (1984) presented sentences that biased a typical member of a category (e.g., "The guest saw the bird that landed on the branch"--robin) or an atypical member (e.g., "The guest saw the bird that roasted on the grill"--chicken), or that were neutral (e.g., "The guest saw the towels that hung in the bathroom").…”
Section: Semantic Variation and The Irrelevant Wordmentioning
confidence: 99%